Left atrial strain: a new predictor of thrombotic risk and successful electrical cardioversion. Issue 2 (June 2016) - Costa, Cátia; González-Alujas, Teresa; Valente, Filipa; Aranda, Carlos; Rodríguez-Palomares, José; Gutierrez, Laura; Maldonado, Giuliana; Galian, Laura; Teixidó, Gisela; Evangelista, Artur
Abstract : Background: Left atrial deformation (LAD) parameters are new markers of atrial structural remodelling that seem to be affected in atrial fibrillation (AF) and atrial flutter (AFL). This study aimed to determine whether LAD can identify patients with a higher risk of thrombosis and unsuccessful electrical cardioversion (ECV). Methods: Retrospective study including 56 patients with AF or AFL undergoing ECV, with previous transthoracic (TTE) and transoesophageal echocardiography (TEE) studies. Echocardiographic parameters analysed were as follows: left ventricle function, left atrium (LA) dimensions, LAD parameters (positive and negative strain peaks), left atrial appendage (LAA) filling and emptying velocities and the presence of thrombi. Strain values were analysed according to thrombotic risk and success of ECV. Results: Lower mean values of peak-positive strain (PPS) in patients with prothrombotic velocities (<25 cm/s) and a higher incidence of thrombi in LAA were observed compared with those with normal velocities. Multivariate analysis revealed PPS normalised by LA maximum volume indexed by body surface area (BSA) to be associated with prothrombotic risk (odds ratio 0.000 (95% CI: 0.000–0.243), P 0.017), regardless of CHADs2VASC score. Peak-negative strain normalised by LA volumes indexed by BSA were associated with unsuccessful ECV. Conclusions: Atrial deformation parameters identify AF and AFL patients with a high risk of thrombosis and unsuccessful ECV. Therefore, these new parameters should be included in anticoagulation management and rhythm vs rate control strategies.